2016
DOI: 10.1038/srep31904
|View full text |Cite
|
Sign up to set email alerts
|

Drone exposure to the systemic insecticide Fipronil indirectly impairs queen reproductive potential

Abstract: A species that requires sexual reproduction but cannot reproduce is doomed to extinction. The important increasing loss of species emphasizes the ecological significance of elucidating the effects of environmental stressors, such as pesticides, on reproduction. Despite its special reproductive behavior, the honey bee was selected as a relevant and integrative environmental model because of its constant and diverse exposure to many stressors due to foraging activity. The widely used insecticide Fipronil, the us… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
78
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 57 publications
(88 citation statements)
references
References 74 publications
6
78
0
Order By: Relevance
“…This confirmed earlier research by the same authors had shown that queens inseminated with sperm of fipronil exposed drones had less and less viable spermatozoa stored in their spermatheca (Kairo et al 2016). They found that several pesticides, among them fipronil, imidacloprid, and thiamethoxam, reduced sperm viability (in vitro sperm assay).…”
Section: Sublethal Effects On Reproductionsupporting
confidence: 89%
“…This confirmed earlier research by the same authors had shown that queens inseminated with sperm of fipronil exposed drones had less and less viable spermatozoa stored in their spermatheca (Kairo et al 2016). They found that several pesticides, among them fipronil, imidacloprid, and thiamethoxam, reduced sperm viability (in vitro sperm assay).…”
Section: Sublethal Effects On Reproductionsupporting
confidence: 89%
“…The amount of food collected in the feeders was measured daily to assess the effect of fipronil on worker feeding behavior. Regardless of the rearing method, fipronil did not affect the amount of syrup and pollen that was gathered by the bees (data not shown), as was previously observed in bees grown under semifield conditions [26]. A comparison of the amount of food that was gathered by workers between bees reared using different methods was not relevant because the feeding methods were different.…”
Section: Food Collection and Consumptionsupporting
confidence: 67%
“…Hence, exposure to environmental stressors, such as biological or chemical agents, can have different effects on drone life traits and fertility depending on the approach used. To better explore this notion, at least with regard for chemical agents, in the present study, we reared drones with different methods using bees that were or were not exposed to a relevant concentration of the insecticide fipronil, which has been previously shown to have effects on drone fertility under semifield conditions and on the reproductive potential of the queen .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although reports of colony losses due to high rates of queen failure exist, only few studies address direct or indirect physiological effects in queens caused by pesticide exposure 2, 5, 29, 30 . Most studies focused on only three neonicotinoid insecticides, clothianidin, imidacloprid, and thiamethoxam, which are currently subject to a moratorium in the European Union 31 .…”
Section: Introductionmentioning
confidence: 99%